The Protective Effects of Peroxisome Proliferator-Activated Receptor Gamma in Cerebral Ischemia-Reperfusion Injury - Ding, Yanping (Front Neurol, 2020)
Cerebral ischemia-reperfusion injury (CI/RI) is a complex pathological process that often occurs secondary to trauma, surgery, and shock. Peroxisome proliferator activated receptor gamma (PPARγ) is a subunit of the PPAR and is a ligand-activated nuclear transcription factor. After being activated by its ligand, PPARγ can combine with specific DNA response elements to regulate the transcription and expression of genes. It has a wide range of biological functions, such as regulating lipid metabolism, improving insulin sensitivity, modulating anti-tumor mechanisms, and inhibiting inflammation. In recent years, some studies have shown that PPARγ exerts a protective effect during CI/RI. This article aims to summarize the research progress of studies that have investigated the protective effects of PPARγ in CI/RI and the cellular and molecular mechanisms through which these effects are modulated, including inhibition of excitatory amino acid toxicity, reduced Ca(2+) overload, anti-oxidative stress, anti-inflammation, inhibition of microglial activation, maintain the BBB, promotion of angiogenesis, and neurogenesis and anti-apoptotic processes.